Long-run Impact of Globalization, Agriculture, Industrialization and Electricity Consumption on the Environmental Quality of Bangladesh - Daizy, Afia Fahmida; Anjum, Mobasshir; Arman, Md. Raied; Nazia, Tanzina; Shah, Nadir (International Journal of Energy Economics and Policy, 2021)
This study strives to assess the long-run dynamic relationship between carbon emission, and phenomena such as globalization, industrialization, electricity consumption, and agriculture for Bangladesh by utilizing annual Time series data for 1971-2014. To this end, ARDL co-integration approach is utilized in this study to investigate the particularly targeted dynamics. The findings reveal strong positive long-run relation between carbon emission, and globalization, and electricity consumption while exhibiting weak relation between emission, and industrialization. For agriculture, no significant long-run relation could be found. The current economic status of the country is liable for the relation dynamics. Improvement from the existing physical, and governance infrastructure of the country holds the key to mitigating the emission problem generating as a by-product of growth, and globalization in general. Keywords: Climate change; Economic growth; Carbon emission; Energy consumption; Co-integration; Environmental economics. JEL Classifications: C32, F64, Q56 DOI: https://doi.org/10.32479/ijeep.11817